The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1590/s0100-55022009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Atividades grupais reflexivas com estudantes de Medicina

Abstract: As práticas grupais desenvolvidas junto a estudantes de Medicina assumem uma característica de técnica de ensino, oferecendo-lhes um espaço para a reflexão crítica sobre o desenvolvimento de seu papel profissional. Assim, como referencial teórico para o trabalho em grupos, destacamos o sociodrama educacional, caracterizado como uma linha de pesquisa-ação em Psicologia Educacional. O objetivo deste estudo foi avaliar os efeitos de atividades grupais reflexivas com referencial sociodramático desenvolvidas com es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
3
0
6
Order By: Relevance
“…Colares [34] conducted a social-drama research with medical students and found that sharing difficulties inherent to undergraduate medical education with colleagues was beneficial, favouring positive links among the participants as well as the experience of being in the other’s shoes by means of role-playing. All these enabled the students to have a more critical reflection on the development of their professional role.…”
Section: Discussionmentioning
confidence: 99%
“…Colares [34] conducted a social-drama research with medical students and found that sharing difficulties inherent to undergraduate medical education with colleagues was beneficial, favouring positive links among the participants as well as the experience of being in the other’s shoes by means of role-playing. All these enabled the students to have a more critical reflection on the development of their professional role.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos-Cerqueira et al 29 Aragão et al 39 Colares and Andrade 2 Ramos-Cerqueira et al 26 Jucá et al 24 De Marco et al 19 Francischetti et al …”
Section: Studyunclassified
“…After that, the roles were determined and the scenes were enacted. Some difficulties pointed out by the authors were the low enthusiasm of the students in participating in the role playing 2,40 ; resistance to recording the scenes and to feedback 19 ; anxiety and inhibition when acting out the scene in front of colleagues 24 ; difficulty in understanding the organization of the proposed activity and role reversal 40 . In one study, the authors reported that teachers/tutors initiated the scene enactment as a strategy to decrease students' anxiety and resistance 19 .…”
Section: Role Playingmentioning
confidence: 99%
See 1 more Smart Citation
“…As Diretrizes Nacionais dos Cursos de Graduação de Medicina enfatizam a relevância social da comunicação na relação entre médico-paciente em seus diferentes aspectos, conforme se lê a seguir: Da mesma forma, estudos apontam a valorização do tema nas políticas públicas de saúde de acordo com a cultura e currículo médico local 7,8,9 . Assim, torna-se necessário maior investimento no treinamento das entrevistas clínicas desde a formação acadêmica, a fim de facilitar o aprendizado dos estudantes na área da saúde frente à prática comunicacional e relacional [10][11][12][13][14][15] .…”
Section: Introductionunclassified